Estudo experimental e modelo semiempírico de uma válvula de expansão termostática de uma bomba de calor solar a R290 - Arthur Pacheco Luz (2023)
The expansion device is a critical component for heat pump and refrigeration machines operation, its study is a fundamental part of the development of improvements in refrigeration and heating areas. Among the various types of expansion devices, the Thermostatic Expansion Valve (TEV) stands out for its fast response time and to being a purely mechanical component with high capacity in controlling the degree of refrigerant superheating. A semiempirical mathematical model was developed for a TEV installed in a Direct Expansion Solar-Assisted Heat Pump (DX-SAHP) operating with R290 (Propane). The research work was experimental and for this purpose an instrumented DX-SAHP was used. During the experiments, various operating modes of the heat pump were tested for water heating. The tests were performed under the influence of different solar irradiation intensities, outdoor, and without the effect of irradiation, indoor. The operational parameters of the equipment were collected following a single methodology, and at the end of the study, 150 experiments were conducted. The development of the semiempirical model was based on the combination of the base equation existing in the literature, which describes the operation of the TEV, and the conception of an equation through the method of multiple linear regression of parameters evaluated during the experiments, such as solar irradiation incidence, component inlet and outlet pressures, and degree of superheating. As a result, a multiple linear regression with an adjustment higher than 96% was obtained. This regression was combined with the base equation, following what was presented by works in the specialized literature, resulting in a model that showed an adjustment higher than 94%. It was concluded that the semiempirical model performs well in predicting the mass flow rate of the system, even under the influence of different solar irradiation conditions. The model can also be used to compose the overall model of the studied DX-SAHP.